Introduction to planetary geomorphology - Greeley, Ronald (Cambridge University Press, 2013)
"Nearly all major planets and moons in our Solar System have been visited by spacecraft and the data they have returned has revealed the incredible diversity of planetary surfaces. Featuring a wealth of images, this textbook explores the geological evolution of the planets and moons. Introductory chapters discuss how information gathered from spacecraft is used to unravel the geological complexities of our Solar System. Subsequent chapters focus on current understandings of planetary systems. The textbook shows how planetary images and remote sensing data are analyzed through the application of fundamental geological principles. It draws on results from spacecraft sent throughout the Solar System by NASA and other space agencies. Aimed at undergraduate students in planetary geology, geoscience, astronomy and solar system science, it highlights the differences and similarities of the surfaces at a level that can be readily understood by non-specialists"--